(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Sleep is a fundamental physiological process that supports cognitive performance, metabolic balance, immune function, and neurological health. This paper explores three key components of sleep regulation: circadian rhythms, melatonin secretion, and the glymphatic system. The circadian system, governed by the suprachiasmatic nucleus (SCN), synchronizes biological functions with the 24-hour day. Melatonin acts as a hormonal signal aligning sleep with environmental light–dark cycles. Meanwhile, the glymphatic system performs active clearance of metabolic waste from the brain during sleep. Disruption of these mechanisms through lifestyle factors, aging, or disease has significant implications for human health. Understanding the physiology of sleep enables targeted strategies for disease prevention and the promotion of homeostasis.